An Unusual Case of Primary Aneurysmal Bone Cyst of the Patella with a Review of Literature - Girish Mugdum; Rajiv Kaul; Anil Kumar Mishra (Journal of Orthopedics, Traumatology and Rehabilitation)
Tumors of the patella are uncommon. A 28-year-old male, who presented with intermittent knee pain of 9 months duration, with swelling and tenderness over the patella underwent a clinico-radiological evaluation which revealed fluid-fluid levels, suggestive of an aneurysmal bone cyst (ABC). Conventional treatment of ABCs usually consists of curettage and autologous bone grafting. However, in this case, a total patellectomy resulted in full functional restoration and resumption of activities, thereby ascertaining this method as a successful treatment option for primary ABC of the patella.